Process quality in toddler classrooms in four European countries - Cadima, J.; Aguiar, C.; Guedes, C.; Wyslowska, O.; Salminen, J.; Slot, P.; Barata, C.; Lerkkanen, M.-K. (Early Education and Development, 2023)
Research Findings: This study examined whether teacher-child interaction quality varied as a function of type of activity in toddler classrooms in four European countries (Finland, Netherlands, Poland, and Portugal). It also investigated whether specific activity settings, namely levels of adult involvement, use of whole group, and children’s engagement with materials, explained differences in teacher-child interaction quality across activities. Participants were 129 toddler classrooms and their lead teachers, specifically, 28 in the Netherlands, 40 in Finland, 31 in Portugal, and 30 in Poland. Process quality was measured with the CLASS Toddler (La Paro et al., 2012) and the Activity Setting Measure was used to characterize adult levels of involvement, group organization, and children’s engagement with materials. Findings indicated that there were important variations across activities in all countries. Positive associations were found between higher levels of adult facilitation and both Emotional and Educational Support. Other activity settings partially explained differences across activities in interaction quality, although patterns varied by country. Practice or Policy: CLASS scores were conditional on the content and format of the activities. Greater attention to activity types and settings may be a means to increase the precision of quality assessment.